2015
DOI: 10.1136/jech-2015-205948
|View full text |Cite
|
Sign up to set email alerts
|

Widening inequalities in self-rated health by material deprivation? A trend analysis between 2001 and 2011 in Germany

Abstract: Inequality in SRH by material deprivation was relatively stable; however, an observed quadratic trend coincided with active and passive labour market reforms in Germany in early 2005.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 56 publications
2
24
0
3
Order By: Relevance
“…Pheiffer [19] observed that many risk factors for NCDs were not captured in FE regression analysis and noted that important variables can be excluded from analysis by using certain panel analysis methods, leading to distorted results [20,21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Pheiffer [19] observed that many risk factors for NCDs were not captured in FE regression analysis and noted that important variables can be excluded from analysis by using certain panel analysis methods, leading to distorted results [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…In general, panel data are analyzed with an FE regression which addresses the limitations of crosssectional and time-series analyses and considers attributes inherent to survey units [18]. However, since unobserved endogenous attributes are not always associated with observed attributes, a pooled OLS regression should be run on adult population data [20,21,24]. This is in line with the aforementioned finding that important variables that may influence a dependent variable cannot be identified if only an FE panel regression is run on panel data that undergo little change, leading to distorted results [20,21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have observed a close link between poverty and ill health [ 1 4 ], and the risk of getting a longstanding illness increases over the life course [ 5 ]. However, the extent to which illness leads to limitations in everyday life varies according to several factors, including type, stage and intensity of the health problem, personal perception of the situation, and available economic resources.…”
Section: Introductionmentioning
confidence: 99%